Application of crash pulse on the car crashworthiness design. (September 2017) - Teng, Tso-Liang; Chang, Peng-Hsiang; Liang, Cho-Chung; Fung, Da-An
Crash pulse is an acceleration curve measured in the car during a crash test. The shape, time duration, and maximum acceleration of crash pulse may influence the predicted motion of the occupants. The characteristics of crash pulse measured during crash tests can be further used to analyze the crashworthiness of a given vehicle design. Thus, the dummy installation steps can be skipped entirely. This study comprised two parts. First, frontal crash pulse data were analyzed to determine the relationship between crash pulse curves and occupant injuries and identify the types of pulse associated with minimal occupant injury. Second, crash pulses obtained from frontal crash simulations using different bumper and crossmember designs were correlated to original crash pulse curves to assess car crashworthiness and suggest design improvements. Dummy injuries were not directly considered. However, to verify the effectiveness of using crash pulse curves to evaluate design crashworthiness, crash simulations were conducted with dummies, and the severity of dummy head damage was recorded. According to comparison results, the evaluation results of car bumper and crossmember redesign using head injury criterion value with employing crash pulse on crashworthiness design result are identical. It reveals the feasibility of car crashworthiness design based on the crash pulse.